Przejęcie i likwidacja katolickiej organizacji Caritas w województwie wrocławskim w 1950 roku - Włodarczyk, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The take over and liquidation of the charity organization Caritas, both in Poland and in the former province of Wroclaw, lasted for several years after the end of World War II. The consistent cooperation of Caritas with the communist authorities was amicable for a period of approximately three years after the war. It began changing when the Caritas organization started being more and more active in many spheres of charitable work. The communist authorities began to see their main ideological opponent in the Church, which interacted with the society through its charity work, in a competitive way. Thus, in the years 1948–1949, the communist authorities gradually took over the facilities belonging to the ecclesiastical organization, suspended operations of its various branches e.g. Zgorzelec, or completely refused the allocation of premises e.g. Oleśnica. Inspections of Caritas, which were carried out at the time, were biased with the aim of demonstrating the alleged irregularities, manipulations and abuses within this organization e.g. Wrocław, Kamienna Góra, Lubawka, Chełmsk Śląski. The policy of the communist authorities, aiming to completely eliminate the Church’s influence on the society, led to the discontinuation of development of the Church activities and, on 23 January 1950, the authorities definitively took over the charity Caritas from the Church, establishing its coercive management. Since that time, the Catholic organization — Caritas has become the Caritas Catholic Association under the full jurisdiction of the Polish People’s Republic authorities.
Keywords: działalność charytatywna Kościoła; nadzór państwowy nad Kościołem; zarządzanie przymusowe; likwidacja; nacjonalizacja